Interference Between S. Aureus and P. Aeruginosa Clinical Isolates: Interferensi Antara S. Aureus dan P. Aeruginosa Isolat Klinis - Aghadeer Sarmad Najeeb; Nagham Mohamed Khalaf; Israa Salim Kamil (Academia Open, 2024)
General Background: Understanding microbial interactions between Pseudomonas aeruginosa and Staphylococcus aureus is crucial for clinical infections, as they often coexist and influence each other's growth and virulence. Specific Background: Both organisms are known for their ability to form biofilms and exhibit multidrug resistance (MDR), complicating treatment strategies in hospitalized patients. Knowledge Gap: Previous studies have explored the virulence of P. aeruginosa and S. aureus, but there is limited understanding of their direct in vitro interactions, particularly in protease and lipase production. Aims: The study examined the interaction between P. aeruginosa and S. aureus isolates in hospitalized patients' sputum, urine, and blood samples, focusing on virulence factors, biofilm formation, and antibiotic resistance patterns. Results: In Diyala, Iraq, 50 clinical isolates showed P. aeruginosa as protease producers, lipase producers, and biofilm producers, with significant MDR phenotypes in both species. Novelty: This study highlights the ability of P. aeruginosa to produce staphylolysin, offering novel insights into the antagonistic mechanisms that may suppress S. aureus in co-infections. Implications: The study emphasizes the significance of understanding microbial interactions in clinical infections, particularly in biofilm-associated MDR infections, to improve treatment outcomes and guide more effective therapeutic approaches. Highlights: P. aeruginosa staphylolysin inhibits S. aureus growth in vitro. Both bacteria produce biofilms and exhibit multidrug resistance. Microbial interactions impact infection severity and treatment strategies. Keywords: Microbial interactions, Pseudomonas aeruginosa, Staphylococcus aureus, Biofilm, Multidrug resistance